Empirical Validation of the Next-Gen Digital Project Manager Competency Framework Through Exploratory Factor Analysis - Owais, Omar A; Poshdar, Mani; GhaffarianHoseini, Ali; Jaafar, Kamal; Sarhan, Saad (Emerald, 2026)
Purpose Digital transformation is reshaping project delivery in the construction sector, requiring Project Managers (PMs) to operate across increasingly complex technological, organisational, and sustainability-driven environments. Despite the growing importance of digital capabilities, there remains a lack of empirical evidence on the underlying structure of digital project management competencies in construction. This study aims to empirically validate the Next-Gen Digital PM Competency Framework for the construction sector. Design/methodology/approach Building on a previously developed and validated list of 55 digital PM competencies, survey data were collected from experienced construction professionals and analysed using Exploratory Factor Analysis (EFA). Principal Axis Factoring (PAF) with Promax rotation was employed to examine the latent structure of the competency set. Findings The results confirm a statistically robust seven-factor competency structure, supported by eigenvalue thresholds, scree plot interpretation, and thematic coherence. A total of 25 competencies were retained and grouped into seven latent constructs: Digital Execution and Optimisation; Human-Centred Digital Leadership; Lifecycle Risk and Compliance Knowledge; Digital Sustainability Intelligence; Digital Tools Proficiency and Automation; Digital Content and Data Management; and Digital Transformation Enablement Skills. Together, these factors capture the multidimensional nature of digital PM capability across technical, behavioural, and cognitive domains. Originality/value This study provides one of the first empirically validated digital project management competency frameworks tailored to digitally transformed construction environments. The findings demonstrate that digital PM competency extends beyond technical proficiency to encompass leadership, governance-related capabilities (e.g. lifecycle risk and compliance), sustainability, and transformation-oriented capabilities. The resulting framework offers an empirically grounded foundation for competency assessment, workforce development, and targeted professional upskilling in digitally enabled construction environments, while establishing a statistically validated basis for future confirmatory analysis.
Keywords: 33 Built Environment and Design; 3302 Building; 8.1 Organisation and delivery of services; 4 Quality Education; 12 Built Environment and Design; Digital project management; Digital transformation; Competency framework; Exploratory factor analysis (EFA); Construction industry